La casa di Tiofere. Avvio di una ricerca etnografica - Spini, Tito; Antongini, Giovanna (L’Uomo società tradizione sviluppo, 2019)
The authors have already noted in earlier ethnographic surveys that the dwelling represents a concentrated diagram of the components of the internal and external forces of the family nucleus. In this initial study of the Lobi people (Upper Volta), the house of Tiofere in the village of Poltianao has been taken as a representative example. The motivations and ritual involved in choosing the site and laying out the house, the stages of construction, together with the rational/constructional and metaphysical components involved, the prohibitions on the orientation of the dwelling, and the close link between the fundamental events of life and the “house” establish a complex but legible structure. The Lobi house is a fortified entity both in form and as a fabric of tensions and connections woven by the tila (guardian spirits). The house and the land surrounding it are a sample, a microcosm, and a starting point for the study of the layouts of dwellings, the site of the points that register physical and other data Which refer to the family group and its interchange with the outside World.